Review of autoimmune blistering diseases: the Pemphigoid diseases. (11th July 2019) - Daniel, B.S.; Murrell, D.F.
Abstract: Autoimmune Blistering Diseases of the Pemphigoid type is characterised by sub‐epidermal blisters (SEB) with circulating autoantibodies against components of the basement membrane zone (BMZ). The main disorders to date include bullous pemphigoid (BP), pemphigoid gestationis, mucous membrane pemphigoid (MMP), epidermolysis bullosa acquisita (EBA), linear IgA disease (LABD), dermatitis herpetiformis (DH), lichen planus pemphigoides and bullous lupus. This is in contrast to pemphigus and related disorders, which demonstrate intraepidermal acantholysis and a positive Nikolsky sign. The classification and management is based on clinical, histological and direct and indirect immunofluorescence findings. There are, however, overlapping clinical and histological features between the conditions and clinical heterogeneity within each disease.